Cathy Freeman: "one athlete, one nation, two flags" but a multi-dimensional message - Valérie Cruzin (Universidad Politécnica de Madrid, 2024)
On 25 September, 2000, Cathy Freeman won the 400-meter final in her native country. Symbolic on two levels, political (Ory 2000, Nocita 2020) and social (Delporte 1991, White 2012) the image of this victory was on the front pages of the world's newspapers. Indeed, on 25 September, Freeman decided to do her victory lap holding the two flags of her country - Australian and Aboriginal flags - thus breaking rule number 50 of the Olympic Charter. Symbolicallytied together, these two flags then showed to the world her pride at being both Aboriginal and Australian. They also brought to light the Aboriginal people that had been deprived of its rights and lands by the Australian government since this Terra Nulius was conquered in 1788 (Hugues 2003), in a context of reconciliation claims. However, despite some violent reactions (Hugues, 1987), Freeman's gesture, pregnant with political and identity claims (White 2011), was never punished. What differences can be made in this political gesture and the one, thirty- two years earlier made by Tommie Smith, John Carlos and Peter Norman, who were severely disciplined? What does such a seemly clemency say about the Olympics? By replacing this picture in the social and historical context of a country, Australia, and a movement, Olympism, along with a semiotic analysis of the headlines of Australia's national newspapers (corpus), we propose to give a better understanding of what it shows and reveals about the political and community issues at stake, as well as the contradictions it reveals.